Characteristics and outcome of traumatic brain injury in Nabire General Hospital, Papua, Indonesia - I Nyoman Surya Negara; Joni Ribo Tandisau; Amos Nomba (Neurologico Spinale Medico Chirurgico, 2022)
Background: Traumatic brain injury (TBI) is a disruption in the normal function of the brain that can be caused by a bump, blow, or jolt to the head, or penetrating head injury. TBI is a major public health problem that can lead to long-term disability. This study was performed to cognize the clinical characteristic and parameters that could predict the outcome of TBI patients and become the foundations for public health interventions to help prevent and lower the mortality rates of TBI in other rural and remote areas. Methods: This research is a retrospective study. Our patient data were collected from Nabire General Hospital medical records from 1 January 2020 to 31 December 2020. This study included all patients who were diagnosed with TBI and excluded the incomplete data. The study was analyzed using chi-square. Results: This study shows TBI mostly occurs in men and the peak incidence in aged 17-65 years old and mainly caused by road traffic accidents. Some factors significantly shows correlation to predict worse outcomes in TBI patients are impaired oxygen distribution, low GCS score, history of consuming anticoagulant and antiplatelet, and the different types of brain hemorrhage. Conclusion: TBI in Papua mostly occurs in men aged between 17-65 years old and road traffic accidents are the main cause. The impaired oxygen distribution, low GCS score, history of consuming anticoagulant and antiplatelet, and the different types of brain hemorrhage were associated with unfavorable outcomes.